A monograph of Stoebe and Seriphium (Gnaphalieae, Asteraceae) in southern Africa and neighbouring islands - Koekemoer, Marinda (Phytotaxa, 2016)
The genus Seriphium, previously treated as an informal group within Stoebe, is resurrected on the grounds of flower morphology, pollen morphology, and basal resin cavities in the leaves, as well as geographical distribution. The generic circumscriptions of Stoebe (with 18 accepted species) and Seriphium (with 9 accepted species) are revised in southern Africa and neighbouring islands, and five new combinations are proposed in Seriphium. Elytropappus ruscianus, Stoebe burchellii and St. vulgaris are listed as new synonyms in Seriphium, whilst Stoebe copholepis, St. ensori, St. sphaerocephala, St. humilis, St. salteri and St. bruniades are new synonyms in Stoebe. Keys, descriptions and distribution maps are provided for all species.